Validity and reliability of force insoles to measure center of pressure during return-to-sport testing - McNeese, D.; Eisner, C.; Todd, R.; Noehren, B.; Owen, M. K. (Sensors, 2026)
Center of pressure is a valuable biomechanical variable, predicting joint loading contributions during movement and giving insight into compensatory patterns. The purpose of this study was to assess the validity and reliability of force insoles in calculating vertical ground reaction force and center of pressure during return-to-sport jump testing. Ten healthy individuals performed double- and single-leg vertical and horizontal jumps on an instrumented treadmill while wearing instrumented force insoles. Vertical ground reaction force and anterior-posterior and medial-lateral center of pressure were collected at peak vertical ground reaction force from both devices. Repeat testing occurred 7 ± 5 days following the initial session. Force insoles were valid for measuring vertical ground reaction force (mean absolute error (MAE): 4.34 N/kg) and anterior-posterior center of pressure (MAE: 10% foot length) but were not valid for medial-lateral center of pressure (MAE: 50% foot width). During double-leg vertical, single-leg vertical, double-leg horizontal, and single-leg horizontal jumps, force insoles demonstrated good reliability for measurements of vertical ground reaction force (ICC: 0.89, 0.75, 0.89, and 0.91), anterior-posterior center of pressure (ICC: 0.88, 0.89, 0.94, and 0.97), and medial-lateral center of pressure (ICC: 0.72, 0.09, 0.82, and 0.73). Force insoles are a valid and reliable alternative to evaluating vertical ground reaction force and anterior-posterior center of pressure during return-to-sport jump testing.